The shaping of an ibadah friendly hospital : learnings from the bimaristan of the evergreen past and the practicality of today’s demands - Mohd Nawawi, Norwina; Sapian, Abdul Razak; Abdul Rani, Mohammed Fauzi; Wan Ismail, Wan Zainuddin; Othman, Norliah (2012)
The history of medicine and the healing environment we promote today in healthcare design is not a new phenomenon. It has been a continuous effort through centuries by caregivers that recognizes environment as contributing factors to human wellbeing with or without scientific evidences, to provide appropriate environment under their care. It is an intuitive, honest and sincere consideration that reflects the caring environment of people of that day based on their faith and not on any gains. Today, with advance medical technology and the circumstantial demand of healthcare services and industry, hospitals begin to mushroom seemingly beautiful but without the soul. Why is this so? Although the answer to the question lies on the basic intention or niyah, the transparent process of implementation, clear design outcomes that support the functions and finally the acceptance of the people-users and caregivers, the live on-going experiment on a teaching hospital for International Islamic University Malaysia (IIUM), as an Ibadah Friendly Hospital, will hopefully be the testament to this enquiry. This paper thus intends to share the findings on what makes the hospital with a soul or Ibadah friendly. Ibadah means to do good deeds and actions for Allah's blessings only. It is a spiritual connotation and fundamental way of life for those who submit to Islam. For the purpose of this design based paper, a vivid description on the initial conception of the hospital project for IIUM, based from learning of the bimaristan, the shariah or Islamic law and industry experiences were extracted. Through qualitative approach of literature reviews, observations, discussions, workshops, interviews and meetings from all parties (user-client of academic background, and the contractors (with design consultants)) team under the Private Public Partnership (PPP) procurement system, findings made through project briefing, design development to current development stage prior construction were consolidated. As a design based paper, exclusions to details irrelevant in the discussion is intentional. Though preliminary as the hospital is yet to be built, in the spirit of Ibadah, the findings made should be shared and discuss in the shaping of a hospital of the future, with a soul. Wallahualam,